PENERAPAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DALAM ANALISIS RISIKO KEGAGALAN RADIO LOKOMOTIF DI DIVISI REGIONAL III PALEMBANG - Rizal, Yus; Sunaryo, Sunaryo; Oktaria, Dhina Setyo; Prameswari, Galuh Anggun; Arifianto, Teguh (Jurnal Media Elektro, 2025)
Locomotive radios serve as a crucial telecommunications system in railway operations. However, in Divisi Regional III Palembang, frequent malfunctions occur without systematic damage documentation, resulting in the absence of an optimal maintenance strategy. This study applies the Failure Mode and Effect Analysis (FMEA) method to identify failure characteristics, analyze their impact on each component, and determine the appropriate maintenance strategy. The analysis results indicate that from 2019 to 2022 a total of 20 communication failures occurred with the highest failure frequency observed in the Locomotive Transceiver Unit (LTU), which failed 14 times. The Mean Time Between Failure (MTBF) calculations reveal that the LTU has an average failure interval of 1,253 hours, while the Console has 1,297 hours, and the antenna reaches 8,064 hours. Risk analysis using FMEA shows that the console has the lowest risk level with a value of 18, the antenna has a moderate risk level with a value of 27, and the LTU has the highest risk level with a value of 36. Based on the identified maintenance strategy, the proposed solution includes implementing preventive maintenance and corrective maintenance to mitigate potential failures. A reliability test conducted over 1,000 hours yielded a reliability probability of 18.3%.